2012
DOI: 10.1128/jvi.00742-11
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Cells Sense Influenza A Virus Infection through MDA5 and CARDIF Signaling Involving LGP2

Abstract: Avian influenza viruses (AIV) raise worldwide veterinary and public health concerns due to their potential for zoonotic transmission. While infection with highly pathogenic AIV results in high mortality in chickens, this is not necessarily the case in wild birds and ducks. It is known that innate immune factors can contribute to the outcome of infection. In this context, retinoic acid-inducible gene I (RIG-I) is the main cytosolic pattern recognition receptor known for detecting influenza A virus infection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
168
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(183 citation statements)
references
References 61 publications
14
168
0
1
Order By: Relevance
“…Additionally, RIG-I was highly upregulated in ducks infected with HPAIVs, and slightly upregulated in ducks infected with LPAIVs (Barber et al, 2010). Studies have also demonstrated that the NS1 protein of AIV could inhibit IFNB signaling due to its interaction with MDA5 signaling pathway and RIG-I signaling pathway (Guo et al, 2007;Liniger et al, 2012). According to these reports, different susceptibility of the two species to the suppressive effect of the H9N2 NS1 gene on the IFNB expression may account for different levels of IFNB expression in ducks and chickens, which shared similarities to the results described by Adams et al (2009) despite the fact that our study selected different tissues, different experimental approaches, time points, and LPAIV subtypes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, RIG-I was highly upregulated in ducks infected with HPAIVs, and slightly upregulated in ducks infected with LPAIVs (Barber et al, 2010). Studies have also demonstrated that the NS1 protein of AIV could inhibit IFNB signaling due to its interaction with MDA5 signaling pathway and RIG-I signaling pathway (Guo et al, 2007;Liniger et al, 2012). According to these reports, different susceptibility of the two species to the suppressive effect of the H9N2 NS1 gene on the IFNB expression may account for different levels of IFNB expression in ducks and chickens, which shared similarities to the results described by Adams et al (2009) despite the fact that our study selected different tissues, different experimental approaches, time points, and LPAIV subtypes.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, different IFNB expression levels were observed between ducks and chickens. Recent studies have shown that the chicken melanoma differentiationassociated protein 5 (chMDA5) strongly activated chicken IFNB promoter in response to AIV infection (Liniger et al, 2012), while retinoic acid-inducible gene I (RIG-I) present in ducks, which is apparently absent in chickens, played an essential role in the IFNB production triggered by AIV. Additionally, RIG-I was highly upregulated in ducks infected with HPAIVs, and slightly upregulated in ducks infected with LPAIVs (Barber et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Barber and coworkers (17) characterized the function of duck RIG-I and suggested that the lack of RIG-I in chickens results in deficiency of the antiviral innate immune response induced by this pathway. However, Liniger et al (15) suggested that although RIG-I is missing in chicken cells, chicken MDA5 functionally compensates for the absence of RIG-I in sensing AIV.…”
mentioning
confidence: 99%
“…MDA5 senses essentially positive-strand RNA viruses, in particular members of the Picornaviridae and Flaviviridae families (12)(13)(14). However, MDA5 also can be triggered by certain negative-strand RNA viruses such as members of the Paramyxoviridae family (13) and avian influenza virus (AIV) (15).…”
mentioning
confidence: 99%
“…Although LGP2 was initially assumed to negatively regulate RLR-mediated signaling [40,41], more recent studies revealed a positive role for LGP2 in the regulation of type I IFN responses [42]. Nevertheless, experimental data of further studies are still controversial, with both overexpression and knockdown of LGP2 resulting in type I IFN production [43]. Whether LGP2 mediated signaling can be induced by IVT mRNA remains to be established.…”
Section: In Vitro Transcribed (Ivt) Mrnamentioning
confidence: 99%